A justification of basic income beyond a theory of justice - Giacomo Pisani (Oñati Socio-Legal Series)
Most theoretical positions in support of basic income draw on a “fair society” model. Even in a post-Marxist context, basic income is conceived as a formal recognition of a social relationship, aimed at validating a liberation process that has already taken place. The present work begins from an alternative perspective. In line with a dialectical and conflicting concept of basic income, it proposes a mechanism for the reappropriation of the decision-making process, which opens up spaces for deconstruction and conflict. However, the concept must be calibrated for the conditions in which the right to a basic income is claimed; it must also take account of prevailing power relations. The paper presents a theory of a basic income as a liberation mechanism that facilitates the disarticulation of the mercantile organization of social relations and favours the possibility of autonomously deciding one’s future and the conditions of communal life.